Preliminary - García Aristizábal , Edwin Fabián; Vega posada, Carlos Alberto (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
We are pleased to announce that in December 2013, Revista Facultad de Ingeniería Journal was re-indexed by COLCIENCIAS in Category A1, in the National Bibliographic Index – Publindex, for the years 2013 and 2014. Our Journal has maintained this classification for the last 7 years, which validates the quality of the scientific papers published in it, and the national and international visibility and reputation that the Journal has been gained. This classification recognizes our Journal, once again, as one of the most important Journals in Latin-American in the area of Engineering and Technology.